(untitled) (KYAMC Journal, 2026)
Helicobacter pylori (H. pylori ) is among the most prevalent bacterial pathogens globally and is well recognized for its role in gastrointestinal disorders. Emerging evidence indicates that its impact may extend beyond the digestive system, with potential associations involving extra-gastric conditions, including genitourinary (GU) diseases. This review seeks to critically evaluate the existing literature on the relationship between H. pylori infection and various GU disorders, and to explore the biological mechanisms that may explain this association. Accumulating studies suggest a possible link between H. pylori infection and conditions such as male infertility, prostatitis, benign prostatic hyperplasia, erectile dysfunction, and certain urological cancers. The proposed mechanisms include chronic systemic inflammation, immune system alterations, oxidative stress, endothelial dysfunction, and molecular mimicry, which may collectively contribute to GU pathophysiology. Nevertheless, the current body of evidence remains inconsistent, largely due to methodological variability and limited mechanistic investigations. Robust, well-structured epidemiological and clinical studies are required to confirm causality and to determine the clinical relevance of these potential associations. KYAMC Journal Vol. 16, No. 03, October 2025: 146-151.